Biomass as a means of achieving rural energy self-sufficiency: a concept. Issue 3 (29th October 2021) - Vijay, Vandit; Chandra, Ram; Subbarao, P.M.V.
Abstract : Purpose: To better understand bioenergy's role in sustainable rural development and cleaner environment, it is necessary to place it in a local regional context. This paper aims to provide a conceptual approach for biomass-based energy self-sufficiency in rural areas of developing and underdeveloped countries having a strong agricultural sector. It further provides a framework for the estimation of surplus biomass and bioenergy potential and the biomass power emissions in a rural area. Design/methodology/approach: A detailed approach is laid out to attain energy self-sufficiency in rural areas encompassing identification of surplus biomass resources in a selected area, suitable conversion technologies, consideration of local end-use priorities, skill development and monitoring of the project. Findings: Following the novel approach proposed in this paper a case study analysis for Thanagazi block (Alwar District, India) is done, and it is observed that locally available biomass in the block can substitute more than 75% of the conventional energy demand and save 78% emissions vis-à-vis equivalent coal power. This indicates that creating local bioenergy production system as a means of substituting/complementing fossil energy can contribute to a cleaner self-sufficient ecosystem. Originality/value: Biomass is a spatio-temporal resource. Prior works have looked at bioenergy potential for national or state levels; however, granular data to reveal a more realistic outlook in a rural area is the novelty of this work. Furthermore, biomass assessment studies largely focus on crop residual biomass, whereas the present study also includes livestock manure assessment which is a major resource in rural areas. This paper highlights the need and the approach for exploring locally available biomass to meet the local energy demands for clean energy security while considering the involvement of the local population in bioenergy planning and implementation.